2023
DOI: 10.3390/gels9070571
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Preparation and Research Progress of Photosensitive Antibacterial Complex Hydrogels

Abstract: Hydrogels are materials consisting of a network of hydrophilic polymers. Due to their good biocompatibility and hydrophilicity, they are widely used in biomedicine, food safety, environmental protection, agriculture, and other fields. This paper summarizes the typical complex materials of photocatalysts, photosensitizers, and hydrogels, as week as their antibacterial activities and the basic mechanisms of photothermal and photodynamic effects. In addition, the application of hydrogel-based photoresponsive mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 152 publications
0
1
0
Order By: Relevance
“…These materials are becoming important as a promising solution for wound management due to their tunability, softness, permeability, biocompatibility, or biodegradability. In the context of drug delivery, hydrogels benefit from their porosity, which enables drug encapsulation within a 3D polymeric network. Some antibacterial hydrogels have been particularly valuable in the context of light-induced therapies such as antimicrobial photodynamic therapy (aPDT). aPDT combines light, molecular oxygen, and a photosensitizer to generate reactive oxygen species (ROS) that oxidize lipids, proteins, DNA, and other biomolecules, leading to bacterial inactivation. Good transparency is, therefore, needed for hydrogels to perform well in aPDT, especially for wound dressing applications, and previous work has focused on optimizing their optical properties. , It was shown that electron-beam polymerized polyethylene glycol diacrylate (PEGDA) hydrogels have a higher transmittance over a broader wavelength range compared to their UV-cured counterparts, reaching values well above 90% …”
Section: Introductionmentioning
confidence: 99%
“…These materials are becoming important as a promising solution for wound management due to their tunability, softness, permeability, biocompatibility, or biodegradability. In the context of drug delivery, hydrogels benefit from their porosity, which enables drug encapsulation within a 3D polymeric network. Some antibacterial hydrogels have been particularly valuable in the context of light-induced therapies such as antimicrobial photodynamic therapy (aPDT). aPDT combines light, molecular oxygen, and a photosensitizer to generate reactive oxygen species (ROS) that oxidize lipids, proteins, DNA, and other biomolecules, leading to bacterial inactivation. Good transparency is, therefore, needed for hydrogels to perform well in aPDT, especially for wound dressing applications, and previous work has focused on optimizing their optical properties. , It was shown that electron-beam polymerized polyethylene glycol diacrylate (PEGDA) hydrogels have a higher transmittance over a broader wavelength range compared to their UV-cured counterparts, reaching values well above 90% …”
Section: Introductionmentioning
confidence: 99%